Generating Trust Through Law? Judicial Cooperation in the European Union and the “Principle of Mutual Trust” - Wischmeyer, Thomas (German law journal, 2016)
For a long time, EU institutions have emphasized the connection between one of the most important concepts of the integration method, mutual recognition, and the presence of mutual trust between EU Member States. Only recently, the ECJ reaffirmed in its Opinion 2/13 that mutual trust is at the heart of the EU and a “fundamental premiss” of the European legal structure. But can law really restore, advance or even govern by trust? This question is crucial for the EU of today, which finds itself in the midst of a severe crisis of trust. For the EU as a community “based on the rule of law” generating trust through law might seem the natural, maybe the only politically viable response to a crisis of trust. Nevertheless, even if one agrees that the rule of law requires people to place trust in legal rules, and that courts and administrative agencies need to trust each other in order to work efficiently and consistently, how would legal rules be able to generate or promote trust? Moreover, isn't it deeply rooted in our ideas about constitutional government that democratic law must institutionalize mutual distrust rather than govern by trust? These conceptual and normative objections did not stop the European Union from pursuing the project of trust-building through law in one of the most sensitive areas of EU law, judicial cooperation in civil and criminal matters. This Article will ask whether the project to promote trust through law is a promising one, and, eventually, how to reinterpret statutory provisions and legal principles that purport to generate trust amongst their addressees.